Hambatan Budaya Dalam Kesehatan Anak - Latifah, Latifah (Musawa Jurnal Studi Gender dan Islam, 2006)
This article argues the cultural values have its potention as a hindrance of children health, both psychologically and physically. Cultural value that has its significant influence in children educational system is the perception and parental values of the parent in front of the children. Almost most of the parents are, generally, expecting their children's "advantage". This expectation made children seen as family's "property". The consequenced is parent love their children with certaint "condition". This conditional love is apparent that made children felt that they are not in love and rejected. In tum it makes the children self image diminutive and they are less able to love themselves. This circumstance creates self defence and searching for love mechanism that had it impact on children mental health, particularly for girls, in which they were still in subordinated position within family and society. Not to say that cultural values too still block the children physical health, mostly girls, even since in the mother's womb. Finnaly, this article also sees the cultural dimension of children reproduction health.